2004
DOI: 10.1111/j.1538-7836.2004.00601.x
|View full text |Cite
|
Sign up to set email alerts
|

ADAMTS‐13 activity in plasma is rapidly measured by a new ELISA method that uses recombinant VWF‐A2 domain as substrate

Abstract: To cite this article: Whitelock JL, Nolasco L, Bernardo A, Moake J, Dong J-F, Cruz MA. ADAMTS-13 activity in plasma is rapidly measured by a new ELISA method that uses recombinant VWF-A2 domain as substrate. J Thromb Haemost 2004; 2: 485-91.Summary. The metalloprotease ADAMTS-13 cleaves von Willebrand factor (VWF) at the Y842/M843 peptide bond located in the A2 domain. Measurement of ADAMTS-13 activity is a clinical utility for thrombotic diseases, but the current assays used for diagnostic and clinical resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
48
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 31 publications
1
48
0
Order By: Relevance
“…on April 10, 2019. by guest www.bloodjournal.org From domain. For example, we reported that the A2 domain can be effectively cleaved by ADAMTS-13 in plasma, [45][46][47] implying that the plasma vimentin, which binds to the A2 domain (supplemental Figure 1C), does not impair the cleavage activity. Moreover, the A2 domain bound to vimentin was detected with the monoclonal antibody VP-1, which recognizes a sequence in the N-terminal side next to the ADAMTS-13 cleavage site in the A2 domain, and it is a potent blocker of ADAMTS-13 activity.…”
mentioning
confidence: 96%
“…on April 10, 2019. by guest www.bloodjournal.org From domain. For example, we reported that the A2 domain can be effectively cleaved by ADAMTS-13 in plasma, [45][46][47] implying that the plasma vimentin, which binds to the A2 domain (supplemental Figure 1C), does not impair the cleavage activity. Moreover, the A2 domain bound to vimentin was detected with the monoclonal antibody VP-1, which recognizes a sequence in the N-terminal side next to the ADAMTS-13 cleavage site in the A2 domain, and it is a potent blocker of ADAMTS-13 activity.…”
mentioning
confidence: 96%
“…Binding sites for platelet GPIb␣, heparin, sulfatides, and collagen (5)(6)(7)(8)(9) are within the A1 domain, whereas its homologous A3 domain only binds to collagen, and the A2 domain contains the cleavage site for the metalloprotease ADAMTS-13 (10 -12). The functions of these A domains relevant to the biology of VWF have been characterized by individual recombinant expression of each of the A domains (9,10,13).…”
mentioning
confidence: 99%
“…6,8 Several assays have been developed which rapidly detect ADAMTS13 activity and help to confirm a clinical suspicion of TTP. [10][11][12][13][14] An enzyme-linked immunosorbent assay (ELISA)-based test has also been used to measure ADAMTS13 antigen levels. 15,16 While ADAMTS13 activity measured at the onset of TTP is known to help to confirm the diagnosis, the clinical value of ADAMTS13 antigen measurements in the evaluation of TTP disease severity, responses to therapy, and clinical outcomes has not been well studied in a large cohort of TTP patients with longitudinal follow-up.…”
Section: Introductionmentioning
confidence: 99%